Features Of Advertising As A Functional Variant Of Speech - Ibraimova, Orzigul (TLEP – International Journal of Multidiscipline, 2025)
This article is devoted to a comprehensive consideration of advertising as a multifaceted phenomenon that has a significant impact on various aspects of modern life. Different approaches to defining advertising are analyzed, ranging from dictionary definitions to more detailed scientific interpretations. Particular attention is paid to the linguistic aspect, where advertising is considered as a functional variety of speech with specific stylistic features and language means that stimulate speech activity and trade. The necessity of a scientific approach to advertising communication in order to achieve its maximum effectiveness is emphasized.